Total intravenous anaesthesia using propofol and sufentanil allows controlled long-term ventilation in rabbits without neuromuscular blocking agents. (June 2017) - Reupke, Verena; Walliser, Karoline; Perl, Thorsten; Kimmina, Sarah; Schraepler, Anke; Quintel, Michael; Kunze-Szikszay, Nils
The aim of this study was to evaluate a total intravenous anaesthesia (TIVA) protocol using propofol and sufentanil without neuromuscular blocking agents (NBAs) for a non-recovery lung pathology study in rabbits including 10 h of pressure-controlled ventilation. TIVA was started with 20 mg/kg/h propofol and 0.5 µg/kg/h sufentanil. The depth of anaesthesia was assessed by reflex testing and monitoring of spontaneous movements or respiratory efforts. Vital parameters were monitored to assess the effects of the TIVA protocol. The infusion rates were increased whenever reflex testing indicated inadequate depth of anaesthesia, and were reduced when vital parameters indicated unnecessarily deep levels. Median infusion rates of 35 mg/kg/h propofol and 2.0 µg/kg/h sufentanil were needed to ensure an adequate depth of anaesthesia. This protocol suppressed spontaneous movements, breathing and palpebral reflexes, but was unable to suppress corneal and pedal withdrawal reflexes. Since significant drops in arterial blood pressure (ABP) were observed and the animals were not exposed to painful procedures, positive corneal and pedal withdrawal reflexes were tolerated. In conclusion, propofol and sufentanil is a suitable combination for long-term anaesthesia in non-recovery lung pathology models in rabbits without painful procedures. ABP must be monitored carefully because of the circulatory side-effects, but it is an inappropriate surrogate marker for depth of anaesthesia. Due to the lack of neuromuscular blockade this TIVA protocol allows the adjustment of infusion rates based on reflex testing. The resulting decreased risk of unnoticed awareness is a decisive refinement in anaesthesia for similar studies including long-term mechanical ventilation in rabbits.